Study of ethical issues of green procurement in Indian automobile industry using integrated ISM-fuzzy MICMAC – AHP –VIKOR. (4th September 2020) - Ray, Ankita; Khaba, Sorokhaibam
Abstract : Purpose: The purpose of this study is the identification and analysis of key ethical issues of green procurement (GP) and the potential solutions to mitigate the issues in the Indian automobile sector. Design/methodology/approach: Based on the literature review and expert elicitation, 23 ethical issues of GP in the Indian automobile industry and 11 solutions to mitigate these issues were identified. This paper explores the ethical issues based on an integrated method consisting of interpretative structural modelling fuzzy Matrice d'Impacts Croisés-Multiplication Appliquée á un Classement, analytical hierarchy process and the solutions to mitigate these issues using fuzzy VlseKriterijumska Optimizacija I Kompromisno Resenje. Findings: The findings suggest that ethical issues such as favouritism towards suppliers and failure to fulfil business objectives by top management are identified as the most significant variables with the highest importance weights, while top management commitment for ethical behaviour is identified as the most potent solution for mitigating the issues. Research limitations/implications: This study is limited to the literature review and experts' opinions. Practical implications: The results may help practitioners and researchers to focus on major ethical issues of GP to strategize proactive solutions that may help to mitigate or eliminate the ethical issues. Originality/value: This paper is an original contribution of the analysis of GP and provides an interesting insight into the Indian automotive industry.